Hot-air drying characteristics of red pepper - Doymaz, I; Pala, M (ELSEVIER SCI LTD, 2002)
This work presents a theoretical and experimental study of the drying kinetics of red peppers under different pretreatment and air drying conditions. Red peppers. Capsicum annuum. grown in the region of Kahramanmaras, Turkey, were pretreated with various solutions of alkaline emulsion of ethyl oleate (AEEO) and dried afterwards. To date, there has been no work that studied the effect of AEEO pretreatment solution on the drying of red peppers. Our results indicated that pretreated peppers dried faster and had higher Hunter L (lightness), +a (redness) and +b (yellowness) values than the untreated and dried peppers. 2% ethyl oleate and 5% K2CO3 solution was found to be the most effective dipping solution that provided for whole peppers dried at 50 degreesC, and yielded best color quality. Drying curves of sliced peppers were obtained using the Page and exponential equations. Comparing the r(2) values of both equations, it was concluded that the Page equation represents drying characteristics better than the exponential equation. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: drying; red pepper; pretreatment solution; modelling; CAPSICUM-ANNUUM; SOLAR DRYER; CULTIVARS; Engineering; Food Science & Technology